Biomimetic Networks with Enhanced Photodynamic Antimicrobial Activity from Conjugated Polythiophene/Polyisocyanide Hybrid Hydrogels. Issue 7 (9th January 2020) - Yuan, Hongbo; Zhan, Yong; Rowan, Alan E.; Xing, Chengfen; Kouwer, Paul H. J.
Abstract: Hybrid biomimetic hydrogels with enhanced reactive oxygen species (ROS)‐generation efficiency under 600 nm light show high antibacterial activity. The hybrid gels are composed of helical tri(ethylene glycol)‐functionalized polyisocyanides (PICs) and a conformation‐sensitive conjugated polythiophene, poly(3‐(3′‐ N, N, N ‐triethylammonium‐1′‐propyloxy)‐4‐methyl‐2, 5‐thiophene chloride) (PMNT). The PIC polymer serves as a scaffold to trap and align the PMNT backbone into a highly ordered conformation, resulting in redshifted, new sharp bands in the absorption and fluorescence spectra. Similar to PIC, the hybrid closely mimics the mechanical properties of biological gels, such as collagen and fibrin, including the strain stiffening properties at low stresses. Moreover, the PMNT/PIC hybrids show much higher ROS production efficiency under red light than PMNT only, leading to an efficient photodynamic antimicrobial effect towards various pathogenic bacteria. Abstract : Hybrid biomimetic hydrogels with enhanced reactive oxygen species (ROS)‐generation efficiency under 600 nm light show high antibacterial activity. Additionally, the hybrid gels closely mimic the mechanical properties of biological gels, such as collagen and fibrin, including the strain‐stiffening properties at low stresses.